Pembentukan Taman Baca Untuk Meningkatkan Kreativitas Anak, Pendidikan dan Nilai Agama - Rijadi, Puti Khairani; Budi, Yeniasari Rizkia; Kusumawardhani, Trisnawati (Lembaga Dongan Dosen, 2025)
Reading parks are a vital means of supporting the development of children's creativity, education, and the strengthening of religious values. This community service aims to enhance the reading culture among children by providing an interactive space that facilitates access to a variety of reading materials. By creating a supportive environment, children can develop their imagination and creativity through reading activities and interactions with books. Additionally, reading parks serve as educational media that integrate religious values, ensuring that children gain not only general knowledge but also a strong moral understanding. The methods used include observation, interviews, and data analysis to evaluate the impact of reading parks on improving children's creativity and educational values. The results of the community service demonstrate an increase in children's enthusiasm for engaging with the books provided, along with various facilities such as study tables and play areas. Moreover, the creation of an educational website accompanied by interactive quizzes further enhances curiosity and critical thinking.